Charity Punishment in Islamic Boarding School to Improving Santri Discipline - Ibnu Habibi; Triyo Supriatno (Nazhruna: Jurnal Pendidikan Islam, 2020)
The purpose of this article is to analyze and describe the charity punishment in improving the discipline of santri at the Al Amin Bojonegoro, Muhammadiyah Islamic Boarding School (MBS). This article uses a type of qualitative research using a descriptive-analytic approach. To obtain the technical data used were observation, interviews, and documentation. The results of this article indicate that the forms of punishment in Al Amin Bojonegoro Islamic Boarding School are t ta'zir, 'iqab, and charity, all of which aim to improve the discipline of students. The charity punishment is more prioritized in enforcing the sentence of santri in various kinds of activities, namely worship activities, teaching and learning activities in class, and activities in the dormitory in terms of shared time and order. This article's results are expected to become a reference material in enforcing discipline in Islamic institutions or informal educational institutions. Further research can be developed on the effectiveness of charity punishment in the domain of santri, which this paper can be used as reference material.